Dynamics of Japan's Trade and Industrial Policy in the Post Rapid Growth Era (1980-2000) (Economics, Law, and Institutions in Asia Pacific,, 2020)
This open access book provides an in-depth examination of Japan's policy responses to the economic challenges of the 1980s and '90s. While MITI's earlier role in promoting rapid growth has been addressed in other studies, this volume, based on official records and exhaustive interviews, is the first to examine the aftermath of rapid growth and the evolution of MITI's interpretation of the economy's changing needs. Covering such topics as the oil shocks, trade conflict with the United States, and the rise and collapse of the so-called bubble economy, it presents a detailed analysis and evaluation of how these challenges were interpreted by government officials, the kinds of policies that were enacted, the extent to which policy aims were realized, and lessons for the longer term. This book is recommended especially to officials of countries concerned about the challenges that follow on high economic growth and to readers interested in Japan's contemporary economic history. .